Tahlīlu al-Ahktā’i al-Kitābīyyati Fī Darsi al-Imlā’ litilmīżāti al-Fashli al-Awwali Fī al-Madrasati al-Mutawasiţati ma’hadi tahfīẓi al-Qur’ān bi ma’hadi al-Amīni Al-Islāmiyya Prenduan - Luthfatul Qibtiyah; Lindawati (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2020)
Problem analysis is the process of identifying and interpreting linguistic problem made by students when learning a foreign language as a second language. Linguistic problem was found in all language skills, including writing skills. In practice, many students were doing some mistakes in writing as like morphological problem, syntax, and dictation. The purpose of this study is to analyze the forms of Imla problem and the causes of imla problem for students in 1st grade of Ma'had Tahfidz Al-Qur'an Al-Amien Prenduan Middle School and solutions to overcome these problems. This research is qualitative research, with a descriptive-analytic evaluative type. Data collection methods used were documentation and interviews. The data sources were documentation of the writing of 1st grade student of Ma'had Tahfidz Al-Qur'an Al-Amien Prenduan Middle School, imla instructor, and 1st grade student of Ma'had Tahfidz Al-Qur'an Al-Amien Prenduan. Data analysis techniques used in this study were data collection, problem identification, problem classification, problem explanation, and problem evaluation. The results of this study in imla writing problem were writing hamzah washal and qath'i, lam syamsiyah and qomariyah, alif layyinah, and tanwin fathah. While there were two factors for the occurrence of imla writing problems: 1) Internal factors: lack of understanding of the imla theory, poor hearing, unfocused, poor of mufradat, and unable to distinguish letters, long and short. 2) External factors: unfavorable classroom conditions, teacher dictation, unclear teacher's voice and the teacher's explanation of the imla theory were not detailed. The effective solution to reduce these problems is Ishlah Mubasyir (direct improvement) and repeat the explaination for the wrong material. Keywords: Writing Problem Analysis, Imla